Mindset Kewirausahaan bagi Siswa SMA Negeri 1 Kabupaten Seram Bagian Barat - Sinay, Francisca Riconita; Rehatta, Geradin; Louhenapessy, William George Mozes (Jurnal Pengabdian Arumbai, 2025)
SMA Negeri 1 of West Seram Regency faces challenges in developing entrepreneurial learning that is both applicable and contextual. Although the curriculum includes entrepreneurship content, the learning process remains theoretical and has yet to address practical aspects that can holistically shape students' entrepreneurial mindsets. This community service initiative aims to cultivate an entrepreneurial mindset through training and simple digital business simulations. The method employed is Participatory Action Research (PAR) with an educational and participatory approach. Activities were carried out in the form of theoretical training, product-making practice, and digital marketing simulations using social media and online marketplaces. The results showed a 43% increase in students' understanding and a significant transformation in entrepreneurial mindset across eight core aspects: Growth Mindset, innovation, resilience, adaptability, risk-taking, proactiveness, creativity, and visionary thinking. The program also led to the establishment of a student entrepreneurship club as a sustainability platform. This intervention has proven effective in building a contextual and sustainable school-based entrepreneurship ecosystem.